Description of Health and Clean Life Behaviors and Improving Student Cognitiveness in Islamic Primary School - Pramusinta, Linda; Yuniastuti, Ari; Rahayu, Sri Ratna (Universitas Negeri Semarang, 2021)
Health and Clean Life Behaviors (CHLB) should be applied in daily life so that diseases cannot easily infect human. Children aged from 7 until 14 years have to be taught with CHLB concretely and theoretically. This research explores the general CHLB of Islamic Primary School Gunungpati, Semarang, and to improve CHLB cognition by applying Asset-based Community Development (ABCD). This research applied the mixed-method of qualitative and quantitative methods. The sample of the research consisted of the fifth-graders of the school. They were taken by purposive sampling.Ã‚Â The research subjects consisted of principals, home teachers, sports teachers, and various cognitive categorized learners. The applied instruments were interview guideline and CHLB cognitive test. The techniques of analyzing data were triangulation and test of CHLB cognitive improvement by using N-Gain test. The findings showed that the teaching-learning processes, especially dealing with CHLB, were still teacher-centred learning and lack of maximizing CHLB. In the learners' cognitive improvement test, the learners had improvements with a score of N-Gain test 0.47. It meant the improvement was categorized moderate.